A STUDY OF SKILLS ACQUISITION PROGRAMMES IN GOMBE MEDIUM SECURITY CUSTODIAL CENTRE, GOMBE STATE-NIGERIA - Anas, Nasiru; Abdullahi, Ibrahim; Yerima, Hassan; Agbo, Precious (African Journal of Social and Behavioural Sciences, 2024)
Nigerian Correctional Centre were established as institutions that rehabilitate inmates through various correctional services. One of these correctional services is the skills acquisition programme. The programmes aimed at rehabilitating the prisoners in order to equip them with new skills thereby making them useful to themselves through different activities they engaged in after leaving prisons. This paper therefore examines the availability and functionality of the skills acquisition programmes in Gombe Medium Security Custodial Centre. The methodology employed for this study is the descriptive research method and data was collected from a sample of 294 inmates from the population of 1088 using the Taro Yamani formula for calculating sample size for research activity. The findings of the study indicated that the skills acquisition programmes registered by the inmates include tailoring and cap making, weaving, welding and carpentry, shoe and cream making, bead and soap making, earrings makings and laundry. The study also revealed that majority of the respondents received daily training. Furthermore, the study discovered that the skills acquisition facilities were outdated as shown by the majority views. The study also found that the programmes have relative impact on the inmates. The challenges facing the smooth functioning of the programmes include among others: insufficient training materials, lack of professional skills acquisition tutors and unstable power supply. Finally, the study recommends among others; the need to provide sufficient and updated training facilities, professional skills acquisition tutors and constant power supply by sticking to alternative solar power supply.